MgO saturation analisys of CaO-SiO2-FeO-MgO-Al2O3 slag system - Almeida, Rodolfo Arnaldo Montecinos de (2018)
Electric arc furnace (EAF) slag has a range of functions, including improving energy efficiency through the "slag foaming" phenomenon. As such, the study of slag is important in EAFs. One of the factors that determine foaming quality and efficiency is the presence of solid particles. MgO saturation is highly significant since, in addition to ensuring the presence of solid particles, it also ensures chemical compatibility to minimize refractory consumption. The present study aims to examine MgO saturation, using the software FactSage v.6.4 for all calculations, in the CaO-SiO2-FeO-MgO-Al2O3 slag system and the influence of binary basicity, FeO and Al2O3 content on this system. Ternary diagrams revealed the influence of Al2O3 content on the liquid field and other phases present. Isothermal saturation diagrams (ISDs) were constructed, showing the same dual saturation points found in the ternary diagrams. The ISDs were validated by comparing the results of different heats in terms of the electrical energy consumption. The closer the heat is to the MgO saturation line, the less energy is consumed.